2013
DOI: 10.7554/elife.00435
|View full text |Cite
|
Sign up to set email alerts
|

Structural analyses at pseudo atomic resolution of Chikungunya virus and antibodies show mechanisms of neutralization

Abstract: A 5.3 Å resolution, cryo-electron microscopy (cryoEM) map of Chikungunya virus-like particles (VLPs) has been interpreted using the previously published crystal structure of the Chikungunya E1-E2 glycoprotein heterodimer. The heterodimer structure was divided into domains to obtain a good fit to the cryoEM density. Differences in the T = 4 quasi-equivalent heterodimer components show their adaptation to different environments. The spikes on the icosahedral 3-fold axes and those in general positions are signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
178
1
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 150 publications
(206 citation statements)
references
References 86 publications
(110 reference statements)
15
178
1
12
Order By: Relevance
“…The most obvious characteristic of the fitting results is that the density of the E2-B domain is lower for the 4J21 Fab complex compared with the cryo-EM density for the other E1 and E2 domains. A comparable reduction of the E2-B domain density was observed for the uncomplexed structure (22). This finding indicates that the B domain has greater flexibility relative to the other domains in the uncomplexed structure.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…The most obvious characteristic of the fitting results is that the density of the E2-B domain is lower for the 4J21 Fab complex compared with the cryo-EM density for the other E1 and E2 domains. A comparable reduction of the E2-B domain density was observed for the uncomplexed structure (22). This finding indicates that the B domain has greater flexibility relative to the other domains in the uncomplexed structure.…”
Section: Resultssupporting
confidence: 65%
“…The only previous structural studies of CHIKVantibody complexes were of four neutralizing murine mAbs. Three of these antibodies (m10, m242, and CHK-9) bound to the putative receptor binding sites, whereas one, CHK-152, inhibited the exposure of the fusion loop by immobilizing the E2-B domain (22). Analogous structural studies have been reported for other alphaviruses, such as Ross River virus (27), Sindbis virus (33), and VEEV (34).…”
Section: Significancementioning
confidence: 69%
See 3 more Smart Citations